Second Language Learners' Attitudes towards the Methods of Learning Vocabulary - Zuraina, Ali; Jayakaran, Mukundan; Roselan, Baki; Ahmad Fauzi, Mohd Ayub (Canadian Center of Science and Education, 2012)
The paper aims at investigating students’ learning attitudes after they are exposed to three vocabulary learning methods, namely Contextual Clues, Dictionary Strategy and Computer Assisted Language Learning (CALL). The study involves 123 undergraduates, who were surveyed to identify the factors that affect their attitudes in learning vocabulary using these methods. Findings from the study using ANOVA revealed that students who were exposed to CALL showed more positive attitudes in learning vocabulary compared to other methods. This is due to the tools matching their aptitude for learning. In fact, the tools are regarded as ‘part and parcel’ of the students’ lives. The results of the study also showed that the usefulnessand limitation of the respective methods depend on students’ approaches in using them to learn vocabulary. The implications for language teaching and learning of vocabulary demand practitioners to incorporate the use of computers in their lessons. Nonetheless, they may also integrate the use of Contextual Clues, Dictionary Strategy and CALL in their teaching to accelerate the expansion of students' vocabulary.